Systemic Dynamics of Policy Change: Overcoming Some Blind Spots of Punctuated Equilibrium Theory. - Fernández‐i‐Marín, Xavier; Hurka, Steffen; Knill, Christoph; Steinebach, Yves (Policy Studies Journal, 2022)
In this article, we analyze dynamics of policy change from the perspective of Punctuated Equilibrium Theory (PET). In particular, we investigate how economic crises impact on patterns of policy change in policy areas that vary in terms of their proximity to economic matters: social, environmental, and morality policy. We make two contributions. First, we show that economic crises lead to more incrementalist patterns of policy change in crisis‐remote policy subsystems and make policy punctuations in these areas less likely. However, if such punctuations do occur, they tend to be particularly extreme. Second, we argue that the empirical implications of PET are best tested by separately analyzing variance as an indicator for incrementalism and degrees of freedom as an indicator for punctuations. The empirical analysis builds on two data sets capturing policy output changes in 13 European countries over a period of 34 years (1980–2013).